UPAYA PENINGKATAN KESADARAN HUKUM PENGEMUDI MOBIL DALAM PENGGUNAAN SAFETY BELT - Putra, Donny (UNES Journal of Swara Justisia, 2018)
The duty for used safety belt for drivers and passangers sit beside that of car in the road for safety that drivers and passangers how to managed in the section 106 article (6) ordinance number 22 year 2009 about traffic and street transportation. Duty for used safety belt how to used that, in fact in the field the people still do not care with that, that meaning was consciousness people’s law (driver) for used safety belt still down, Infraction of duty for who do not used this safety belt for does may to punishment with punish during 1 month caged or too much Rp.250.000,- fine appropriate with section 289 ordinance number 22 year 2009 about traffic and street transportation. Based on the regearch method have a quality analysis of descriptive with approachment juridical normative as approachment prime and approachment juridical empirical as proponent prime approachment, that support material and primary data and secondary along with data analysis according to qualitative, writer will search the answers of problem’s law, level of conscionsness car drivers used or do not used safety belt, and effort by unit police traffic at padang city in the cope with infraction of this traffic. The result did this reserach refer to level law conscionsness car drivers was law for used safety belt at the driver in the road, this background situation there are some factors like factor consciousness driver law, law maintenance, background of padang city, how that situation this cars, and sosialiszation traffic ordinance. The effort already that doing by padang’s police in the cope with this traffic infraction was with some approachment there are : preemptive approachment, preventive approachment and repressive approachment.